2020
DOI: 10.1002/er.5669
|View full text |Cite
|
Sign up to set email alerts
|

Ignition of coal‐water fuel droplets with addition of isopropyl alcohol

Abstract: Coal-water fuels have been actively studied in the last decade due to the fact that when they are burned in the furnaces of steam and hot-water boilers, much less anthropogenic oxides of sulfur, nitrogen, and carbon are formed in comparison with coal. The main problem that hinders the widespread introduction of such fuels in the energy sector is long (up to 30 seconds) ignition delay times. Significant (10%-50%) reduction in the ignition delay time is possi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…One of the promising types of fuel for power engineering is coal-water slurries (CWS) [10][11][12]. The amount of pollutants emissions decreases after their combustion [13][14][15][16][17]. But at the same time, the calorific value of such fuel also decreases in comparison with coal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the promising types of fuel for power engineering is coal-water slurries (CWS) [10][11][12]. The amount of pollutants emissions decreases after their combustion [13][14][15][16][17]. But at the same time, the calorific value of such fuel also decreases in comparison with coal.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the literature 13–36 allows concluding that the efficiency of CWS application and successful development of coal‐water technologies depend on the atomization characteristics of such fuels. This is significantly influenced by the component composition of slurries and their properties.…”
Section: Introductionmentioning
confidence: 99%
“…They allow researchers to obtain the most relevant data on expected fuel behavior during actual implementation. However, such works are very scarce and, usually, focus on a chosen aspect of the process like ignition 17 or flame structure. 15 T h i s c o n t e n t i s Complex research on combustion of coal−pyrolysis oil mixtures has not been performed yet.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The cheaper option is blending coal with some highly reactive fuel to promote its ignition. The second component for such a mixture could be brown coal, biomass , and wastes of different types. Recent studies revealed that application of liquid additives allow significant improvement of both ignition and combustion characteristics of initial coal even with a small mass of additive: up to 10 wt % according to ref and up to 5 wt % according to ref (with the optimum value at 3 wt %). Furthermore, it has been theorized that combined application of pyrolysis oil with coal at power plants will allow significant reduction of the contribution to the greenhouse effect.…”
Section: Introductionmentioning
confidence: 99%